(NdIFFERENCIALXNYE URAWNENIQ (B:s (NpRIMERY I ZADA^I (B: (Nu^EBNOE POSOBIE (B/s - (NsAMOJLENKO(B, (NaNATOLIJ mIHAJLOWI^s; (NkRIWO[EQ(B, (NsERGEJ aRSENTXEWI^s; (NpEREST@K(B, (NnIKOLAJ aLEKSEEWI^s ((NmOSKWA (B:s (NwYS[AQ [KOLA(B,s, 1989)
(NbIBLIOGR(B.: (NS(B. 381 (20 (NNAZW(B.)s
Keywords: (NdIFFERENCIALXNYE URAWNENIQs